Research Progress on the Treatment of High - pour - point Oil by Microwave Radiation - Ma, Xiaomei (International Journal of Electric Power and Energy Studies, 2025)
This paper focuses on the all-round research progress of microwave radiation in the field of condensate oil treatment. This paper systematically and deeply analyzes its remarkable results in viscosity reduction and condensation reduction, and explores how to reshape the viscosity characteristics of hypercoagulable oil. Interpret the unique advantages in the dehydration process in detail, and reveal the micro and macro mechanisms of water removal; Comprehensively sort out the internal logic of chemical composition and structural changes, and explore the transformation laws at the molecular level. Present the actual situation of engineering application in detail, and analyze the key points of technology implementation. Through an in-depth analysis of the strengths and weaknesses of existing research and a forward-looking perspective, it aims to lay a solid theoretical foundation for the continuous cultivation of this field, provide guidance with great practical value, help microwave radiation technology achieve breakthrough development in the field of high condensate oil treatment, and promote the petroleum industry to a new level.